Total retroperitoneal approach to aortic reconstruction: A novel technique for aorto-enteric fistulae and graft infections. (23rd February 2018) - Alfawaz, Abdullah; Tashiro, Jun; Sleeman, Danny; Jones, Keith; Rey, Jorge
Aorto-enteric fistulae pose a challenging negative outcome of aortic intervention. Treatment involves graft excision, and recently, more enthusiasm has met in situ revascularization over extra-anatomic bypass. This has been traditionally performed through the transperitoneal approach via a midline abdominal incision. We propose an exclusively total retroperitoneal technique in managing this complication with regard to both the vascular and alimentary tract technical aspects of the procedure. This involves exclusion and bypass of the affected segment followed by en-mass resection of the affected segment with the duodenum, and finally, bowel anastomosis. We present a case of an aorto-enteric fistulae illustrating classical radiological findings treated via a flank incision and retroperitoneal technique after a temporizing endovascular stent placement at an outside institution. Peri-operative course was uneventful. The retroperitoneal approach has been shown to be equivalent to its transperitoneal counterpart in many aspects of treating aortic disease. It has also been shown to be superior in others, including but not limited to, faster return of bowel function, decreased respiratory complications, less blood loss and shorter length of stay in the intensive care unit (ICU) and hospital. We recommend adding this approach to every vascular surgeons operative armamentarium when it comes to managing aorto-enteric fistulae. This might be especially helpful in avoiding re-operative planes, thus minimizing blood loss and iatrogenic bowel injury, better aortic exposure, and adequate access to the duodenum.